External appearance versus internal truth: the Aggadah of Herod in Bavli Bava Batra - Feintuch, Yonatan (AJS review, 2011)
King Herod ruled Judea from 37 to 4 bce. His life and achievements are described in detail in the writings of Flavius Josephus and have been explored in numerous historical studies. In rabbinic literature, however, mention of Herod's image and achievements is scarce. The few sources that do exist are very brief, with the exception of one significant source in the Babylonian Talmud (henceforth: BT), which will be discussed in this article.